Growth Behaviour and New Culm Production in Dendrocalamus Strictus and a Rational Approach towards Management - Tomar, M. S. (Indian Forester, 1963)
Observations on growth and new culm production in Dendrocalamus strictus were recorded in the year 1958 in South Raipur division. Average annual rainfall in this area is about 53" (1346 mm). Bamboos attain a hei~ht of 25'-30' (8 m-l0 m) and a girth of 5"-6" (12-15 cm) at breast height. Newculms start appearing in August. Maximum and lIlinimum growth recorded in 24 hrs. is 10.7" (27.2 cm) and 2.5" (6.3 cm) respectively. Current season's culms were counted in a number of clumps and it was found that the average annual production of new culins and the size of the clump show a linear relationship. This relationship has been made use of in determining the best combination of felling cycle and fellin~ intensity. It has been observed that clumps of various sizes when ,",orked under a particular combination of felling cycle and fellin~ intensity tend to attain a definite size in course of time and thereafter would give a sustained yield (in terms of number of bamboos). Gregarious flowering of bamboos, total cumulative yield during the whole life-cycle and the maximum clump-size, easy for working, have been kept in view while determining the best combination of felling cycle and felling intensity. It has been concluded that if the interval of gregarious flowering is 24 years or more the best combination would be 3 years felling cycle and 4 N felling intensity (retention of :culms four times the number of current season's culms).